2012
DOI: 10.1149/1.3700866
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) New Dielectric Nanomaterials Fabricated from Nanosheet Technique

Abstract: We present a novel procedure for fabricating high-k nanodielectrics by using of perovskite nanosheet (Ca2-xSrxNb3O10) as a building block. We synthesized Ca2-xSrxNb3O10 nanosheets by delaminating layered perovskites (KCa2-xSrxNb3O10), and fabricated multilayer nanofilms on atomically flat SrRuO3 and Pt substrates by Langmuir-Blodgett method. Various microscopy techniques showed highly ordered lamellar structures, and electron energy loss spectroscopy revealed no detectable interdiffusion and strains at the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…However, when the annealing temperature exceeded 600°C, the ε r value of the film decreased, and the film annealed at 800°C showed a small ε r value of 51, probably due to the degradation of the Pt electrode (Figure B). The ε r value of the SNO film grown by the LB method is large, at approximately 240, because this film has a microstructure similar to that of the single crystal . Therefore, it can be suggested that if the crystallinity of the film was improved by controlling the process conditions, the ε r value of the SNO film deposited by the electrophoresis method could be increased.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, when the annealing temperature exceeded 600°C, the ε r value of the film decreased, and the film annealed at 800°C showed a small ε r value of 51, probably due to the degradation of the Pt electrode (Figure B). The ε r value of the SNO film grown by the LB method is large, at approximately 240, because this film has a microstructure similar to that of the single crystal . Therefore, it can be suggested that if the crystallinity of the film was improved by controlling the process conditions, the ε r value of the SNO film deposited by the electrophoresis method could be increased.…”
Section: Resultsmentioning
confidence: 99%
“…To synthesize the nanosheets from these compounds, the alkali metal ions or [Bi 2 O 2 ] 2+ ions of these compounds should be substituted for protons in acid solution, whereas the proton ions should be replaced with organic polycations such as tetrabutylammonium ions (TBA + ) and tetramethylammonium ions (TMA + ) . Finally, these perovskite nanosheets were grown on a substrate using the layer‐by‐layer (LBL), Langmuir‐Blodgett (LB), and electrophoresis methods …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations